2018
DOI: 10.1093/annonc/mdy052
|View full text |Cite
|
Sign up to set email alerts
|

Management of metastatic retroperitoneal sarcoma: a consensus approach from the Trans-Atlantic Retroperitoneal Sarcoma Working Group (TARPSWG)

Abstract: This consensus document combines the available literature regarding the management of multifocally recurrent or metastastic RPS with the practical expertise of high-volume sarcoma centers from multiple countries. It is designed as a tool for decision making in the complex multidisciplinary management of this condition and is expected to standardize management across centers, thereby ensuring that patients receive the highest quality care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 115 publications
0
30
0
Order By: Relevance
“…The variability of all subtypes of sarcomas are not well described due to the heterogeneity of the disease, with subtypes varying in biology, behavior, and treatment responses [36]. The complexity and rarity of sarcomas make them challenging to study as well as medically manage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variability of all subtypes of sarcomas are not well described due to the heterogeneity of the disease, with subtypes varying in biology, behavior, and treatment responses [36]. The complexity and rarity of sarcomas make them challenging to study as well as medically manage.…”
Section: Introductionmentioning
confidence: 99%
“…The complexity and rarity of sarcomas make them challenging to study as well as medically manage. This has driven the development of many long-term institutional, multi-institutional, and national databases that collect epidemiological and clinical data on sarcomas to better understand the disease processes [36]. This study utilizes a nationally representative cancer database, the Surveillance, Epidemiology and End Results (SEER), to study sarcomas in the US over 12 recent years and evaluate trends in epidemiology, management, and survival.…”
Section: Introductionmentioning
confidence: 99%
“…Billingsley et al have advocated complete resection of the metastatic site as a positive prognosis factor for pulmonary metastasis from soft tissue sarcoma and a longer disease-free interval (>12 months) [4]. Moreover, the Trans-Atlantic Retroperitoneal Sarcoma Working Group (TARPSWG) has reported that complete resection of lung metastasis without adjuvant therapy is not an absolute contraindication and occasionally has prolonged survival in selected patients [14]. In the present case, no recurrence was observed after retroperitoneal tumor resection, therefore the upper lobectomy for early lung cancer was sequentially performed four months after the initial operation.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 20-50% of patients will develop metastasis from either bone or soft tissue sarcomas, presenting either as de novo or recurrent advanced disease [ 2 4 ]. Treatment of advanced, metastatic disease includes systemic therapy (such as chemotherapy, targeted therapy, and more recently immunotherapy), radiation therapy, ablation, and surgery [ 5 7 ]. Of the methods, surgical resection of metastasis (metastasectomy) is the accepted standard of care for a select cohort of sarcoma patients, as it is thought that, with careful clinical section, one can achieve long term relapse-free survival and potential cure [ 8 ].…”
Section: Introductionmentioning
confidence: 99%